2020
DOI: 10.3390/ijerph18010014
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdown Restrictions and Online Media Consumption in Germany

Abstract: The lockdown restrictions due to the COVID-19 pandemic have led to increased stress levels and feelings of anxiety in the general population. Problematic usage of certain online applications is one frequent way to compensate for negative feelings and stress. The current study investigated changes of online media consumption during the lockdown in Germany. Gender and age specific differences in specific online activities were assessed. n = 3245 subjects participated in an online survey conducted between the 8th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
2
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(141 citation statements)
references
References 27 publications
5
123
2
11
Order By: Relevance
“…Antes de la pandemia, los participantes reflejaban que sus familias percibían un uso problemático general de las TIC consideradas (salvo en los videojuegos), aumentando estas percepciones durante el confinamiento. Estos resultados coinciden con otros estudios Dong et al, 2020;Lemenager et al, 2021;Wang et al, 2020) que también reseñaron un consumo mayor de las TIC asociado a la pandemia. Atendiendo a los resultados por sexos, los datos reflejan que los hombres tenían un uso más problemático con las TIC que las mujeres antes del confinamiento provocado por el COVID-19, según la percepción de sus familias.…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation
“…Antes de la pandemia, los participantes reflejaban que sus familias percibían un uso problemático general de las TIC consideradas (salvo en los videojuegos), aumentando estas percepciones durante el confinamiento. Estos resultados coinciden con otros estudios Dong et al, 2020;Lemenager et al, 2021;Wang et al, 2020) que también reseñaron un consumo mayor de las TIC asociado a la pandemia. Atendiendo a los resultados por sexos, los datos reflejan que los hombres tenían un uso más problemático con las TIC que las mujeres antes del confinamiento provocado por el COVID-19, según la percepción de sus familias.…”
Section: Discusión Y Conclusionesunclassified
“…Por un lado, ha habido un aumento muy considerable de la utilización de las redes sociales o los servicios de mensajería instantánea (Dong et al, 2020), convirtiéndolas en uno de los principales medios para la comunicación y la construcción de relaciones interpersonales. Este crecimiento ha supuesto una modificación de nuestros patrones de ocio, haciendo que dediquemos mucho más tiempo a la utilización del teléfono móvil con fines de entretenimiento tanto en redes sociales como en otras cuestiones como los juegos en línea y videojuegos (Lemenager et al, 2021). Es reseñable, además, que, pese a lo generalizado de la situación, el consumo parece estar determinado por el género, siendo las mujeres quienes hacen una mayor utilización de los dispositivos móviles (Chóliz et al, 2016;Fernández et al, 2020), mientras que los hombres hacen un mayor uso de los videojuegos (Desai et al, 2010).…”
Section: Introductionunclassified
“…However, as a result of the pandemic and the restrictions on mobility and social contact, the university population that makes up the sample has considerably increased their use of ICTs, reaching addiction patterns in most cases. Authors such as Dong et al (2020), Lemenager et al (2021) or Siste et al (2020) also identified an increase in the use of ICTs linked to the pandemic, without concluding whether this increase is associated with a greater risk of addiction. In this study, the data showed that women had a more problematic use of ICTs than men before the pandemic, a situation that was reversed as a result of the confinement, as men had a more dependent use of technologies than women in the sample.…”
Section: Discussionmentioning
confidence: 99%
“…The survey was created using SoSci Survey Version 2.5.00-i (SoSci Survey GmbH, Munich, Germany). Aside from the assessment of changes in shopping behavior during the lockdown, participants' alcohol consumption, tobacco usage (17), media use (18), and gambling behavior as well as their eating and sport habits were investigated. The survey was promoted via print and social media channels as well as radio interviews and was posted from April 8 to May 11, 2020.…”
Section: Methodsmentioning
confidence: 99%